ESTIMATION OF PHYTOCHEMICAL CONSTITUENTS IN LEAF EXTRACT OF EUCALYPTUS TERETICORNIS CLONES - MANISHA RATHI; ANJANA SHARMA (International Journal of Pharma and Bio Sciences, 2016)
A field trail was conducted to study the chemoprofiling of various phytochemical constituents present in different clones (No. 10, 413, 2040 and 2151) of Eucalyptus tereticornis leaves extract. The study was performed at village Majitha near Bhedaghat district Jabalpur (M.P.) India. Amongst the different clones, clone No. 413 had significantly higher leaf extract of 12.07 and 14.40 per cent with methanol and ethanol, respectively, as compared to other clones. Phytochemical analysis exhibited the presence of tannins, alkaloids and phenols in leaves extracted with methanol and ethanol extractant. Solvent ethanol was more suitable for extraction of various phytochemical constituents present in the leaf extract of Eucalyptus tereticornis. Clone No. 2151 recorded appreciably higher yield of 3.88 and 3.52 per cent of flavonoids in leaves extracted with methanol and ethanol, respectively, whereas Phenol was found to be 2.55 per cent in clone No. 413 followed by 2.41 per cent in clone No. 10 with ethanol.